2013
DOI: 10.7318/kjfc/2013.28.1.078
|View full text |Cite
|
Sign up to set email alerts
|

The Physicochemical Characteristics of Marinated Beef Galbi under Different Cooking Conditions

Abstract: Marinated beef galbi is a traditional Korean dish cooked with soy sauce, pear juice, onion, sesame oil, and sugar. However, there are many differences in beef galbi, including flavor and physicochemical aspects, depending on cooking conditions. Therefore, the physicochemical characteristics of marinated beef galbi prepared through various recipes was evaluated for its effects on pH, texture, aging, proteolysis, heating conditions, cooking time, and flavor compounds (pyrazines, IMPs, or FAAs). There were signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…pH is an important factor that affects the quality of meat, including its freshness, water-holding capacity, tenderness, binding ability, color and texture ( Hong et al, 2013 ; Yim et al, 2016 ). The pH value of PI2 with 2% citric acid was 2.37, and that of PI3 with 2% sodium pyrophosphate was 9.18, while that of PI1 with distilled water was 6.13 (data not shown), suggesting different levels of water-holding capacity or tenderness.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…pH is an important factor that affects the quality of meat, including its freshness, water-holding capacity, tenderness, binding ability, color and texture ( Hong et al, 2013 ; Yim et al, 2016 ). The pH value of PI2 with 2% citric acid was 2.37, and that of PI3 with 2% sodium pyrophosphate was 9.18, while that of PI1 with distilled water was 6.13 (data not shown), suggesting different levels of water-holding capacity or tenderness.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that the water-holding capacity and degree of expansion of the PI2 and PI3 samples are relatively higher than the control (PI1) due to the pH shifting from the isoelectric point (Kim et al, 2000). Hong et al (2013) showed that shifting of pH from pI (isoelectric point) of beef improved the water-holding capacity by as much as 9-15%, followed by an increase in the yield and tenderness of marinated beef meat after cooking. Therefore, the above results correlate with the high water-holding capacity resulting from the pH shift from the isoelectric points and the humectant effect achieved by reducing water loss during drying.…”
Section: Dry Yieldsmentioning
confidence: 99%
See 2 more Smart Citations
“…In China, beef cuts are very popular and widely consumed. It is commonly used for preparing traditional dishes such as Minced Beef Thick Soup, Stewed Beef Brisket with Tomato, Stewed Beef with Carrots, Stewed Beef in Casserole, Stewed Beef Brisket with Radish in Casserole, Boiled Beef Slices, and beef broth combined with various food ingredients (Hong, Kim, Lee, & Heo, ; Kranz et al, ). Beef broth is particularly popular for its palatable taste.…”
Section: Introductionmentioning
confidence: 99%